2017
DOI: 10.1063/1.5005389
|View full text |Cite
|
Sign up to set email alerts
|

Usability evaluation of mobile applications; where do we stand?

Abstract: Abstract. The range and availability of mobile applications is expanding rapidly. With the increased processing power available on portable devices, developers are increasing the range of services by embracing smartphones in their extensive and diverse practices. While usability testing and evaluations of mobile applications have not yet touched the accuracy level of other web based applications. The existing usability models do not adequately capture the complexities of interacting with applications on a mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 22 publications
(27 reference statements)
0
22
0
Order By: Relevance
“…Thus, it is observed that the propagation of various usability assessment models has been introduced in the literature. These models are more general, which may not apply to any specific mobile app due to their complexities and lack of appropriate descriptions on how to choose usability measures such as usability dimensions, criteria and metrics (12) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is observed that the propagation of various usability assessment models has been introduced in the literature. These models are more general, which may not apply to any specific mobile app due to their complexities and lack of appropriate descriptions on how to choose usability measures such as usability dimensions, criteria and metrics (12) .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in general, usability assessment models cannot measure the characteristics of these various apps because each app category has different functional and non-functional requirements. Thus, custom usability models may be required to assess these various apps (12) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, a usable system should be easy to learn and manipulate. In addition, ease of use also refers to the usability and suitability of a system (Zahra et al, 2017).…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…This makes the usability evaluation of tourism applications more demanding. The literature shows the most challenges of mobile application is its interface and some applications are difficult to use based on content and design [4]. Previous studies attempted to evaluate tourism mobile application but they did not propose metrics such as time taken for each task, error capturing and accuracy of each task [5].…”
Section: Introductionmentioning
confidence: 99%